The Organic Architecture as a Democratic Architecture Duhok City as a Case Study - Farha, Rana F.; Tayib, Abdullah Y. (Sulaimani Journal for Engineering Sciences, 2019)
The concept of democracy is old as a term and as an application to the Greek era . Recently, the democracy entered into the developing societies, and affected in all fields , The societies differed in the extent of understanding of the concept in an integrated manner, which was reflected in the application in these societies. The applications of the concept in architecture varied among projects whose designers realized the concept and tried to apply it regardless of the nature of perception, which was directly reflected in the method of application in the practical reality of architecture, ranging from deep understanding and real democratic architecture and others characterized by superficial perception and superficial democratic architecture projects . And other projects characterized by its architecture as a democratic and spontaneous and built without the awareness that the basis of that architecture is very close to the democratic concept, (organic architecture) in this study. The research focuses on this architecture and the extent to which its characteristics correspond to the characteristics of the democratic concept in general and in the city of Dohuk in particular and within the residential sector. These concepts will be compared and applied in areas that represented the architecture of the organic architecture that was built before the entry of democracy into the region and other areas. And other areas were established after the entry of democracy in the province of Dohuk in the Kurdistan Region of Iraq.
Keywords: Democracy; organic architecture; democratic architecture